EFFECT OF ROTATION PATTERN ON HETERODERA AVENAE POPULATION IN WHEAT FIELD - Q. He; A.S. Mo; Z.Q. Qiu; X.B. Zhou; H.Y. Wu (Journal of Animal and Plant Sciences, 2016)
The cereal cyst nematode (CCN; Heterodera avenae) is found in at least 16 provinces in China. CCN often damages wheat and barley, causing severe economic losses. This study investigated the CCN population in a naturally infested field under local climatic and planting conditions. The CCN population spatial distribution between planting rows under rotation crop system was determined. The results showed that distribution of the cysts was relatively uniform at the horizontal scale after several years for same rotation cropping system. When the row spacing was 25 cm, higher cysts were observed in both in and between planting row. Moreover, 79% cysts were distributed in 0–20 cm soil depth. Rotation with maize is beneficial to reduce number of CCN. The results suggested that wheat-fallow system could not decrease number of CCN cysts within 3 years, the specific site for the effective application of chemicals or biological control agents was at 20 cm depth in and between planting rows at harvest time. This information can serve as a reference for the development of an effective and mechanized site-specific management strategy for the control of CCN in large wheat fields.
Keywords: cereal cyst nematode; distribution; row spacing; specific-site control